Magnetite-loaded extracellular polymeric material as well as preparation method and application thereof
By combining the extracellular polymer in the remaining sludge with FeCl3·6H2O, it is prepared with magnetite-loaded extracellular polymer hydrogel material and applied it to the aerobic granular sludge reactor, the problems of long formation period and poor stability in aerobic granular sludge technology are solved, and sludge granulation and system stability are improved.
Patent Information
- Application Number
- CN202411885517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
There are difficult challenges in aerobic granular sludge technology in terms of long formation cycles and poor long-term stability, which leads to difficulties in promoting and using it in industrial applications.
By combining the extracellular polymer in the remaining sludge with FeCl3·6H2O, an extracellular polymer hydrogel material with magnetite loading was prepared and applied to an aerobic granular sludge reactor to promote the granulation of the sludge and the stability of the system.
This method not only effectively promotes the granulation of sludge, improves the stability of the system and decontamination efficiency, but also solves the problem of sludge resource utilization, reduces production costs, and avoids secondary pollution.
Smart Images

Figure CN119707096A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water pollution control engineering, and in particular relates to an extracellular polymer material loaded with magnetite, a preparation method and application thereof. Background Art
[0002] Compared with the traditional activated sludge method, aerobic granular sludge (AGS) technology has attracted the attention of researchers due to its advantages such as fast sedimentation rate and high biological activity. Aerobic granular sludge has great application potential in industrial wastewater and urban sewage treatment due to its high microbial biomass, nitrogen and phosphorus removal capabilities and good sedimentation performance. However, aerobic granular sludge technology also has problems such as long formation cycle and poor long-term stability, which makes it difficult to promote and apply this technology in engineering.
[0003] At present, the main improvement methods for problems such as long formation cycle and poor long-term stability include promoting microbial coagulation to form granular sludge by adding additional divalent or trivalent metal ions, carriers or flocculants, etc., but this method introduces a large number of additional compounds, and there are problems such as high cost, sludge treatment and transportation difficulties. At present, there is also a method of washing out flocculent sludge with poor settling performance by shortening the settling time, but this method easily makes the sludge concentration in the system lower than 1000 mg / L, resulting in a high organic load in the system, which is not conducive to screening out slow-growing microorganisms such as glycogen-accumulating bacteria (GAOs) and phosphate-accumulating bacteria (PAOs). Therefore, how to promote the granulation of aerobic sludge is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] The present invention provides a method for preparing an extracellular polymer material loaded with magnetite, which can prepare an extracellular polymer material loaded with magnetite with excellent performance. The material can effectively and stably promote the granulation of sludge, and effectively solve the problem of resource utilization of excess sludge, which is conducive to reducing production costs.
[0005] The invention also provides an extracellular polymer material loaded with magnetite, which can effectively and stably promote the granulation of sludge.
[0006] The present invention also provides an application method of an extracellular polymer material loaded with magnetite. Applying the extracellular polymer material loaded with magnetite in an aerobic granular sludge reactor helps to promote the formation of aerobic granular sludge and improve the stability and pollution removal efficiency of the system.
[0007] The first aspect of the present invention provides a method for preparing an extracellular polymer material loaded with magnetite, comprising the following steps:
[0008] The excess sludge is mixed with a sodium chloride solution and subjected to a heating treatment to dissociate the extracellular polymers in the excess sludge to obtain a mixed solution; the mixed solution is centrifuged and the supernatant is filtered through a filter membrane to obtain an extracellular polymer mixed solution;
[0009] Add FeCl3·6H2O to the extracellular polymer mixture, stir under ultrasound until the powder is completely dissolved, adjust the pH to neutral, and obtain the first product after vacuum freeze-drying;
[0010] The first product, sodium alginate, polyvinyl alcohol and water are mixed, and then a calcium chloride solution is dropped into the mixture for gelation to obtain hydrogel beads; the hydrogel beads are vacuum freeze-dried to obtain an extracellular polymer hydrogel material loaded with magnetite.
[0011] The preparation method as described above, wherein the mass volume concentration of the sodium chloride solution is 0.8-1%;
[0012] The heating temperature is 75~85℃ and the time is 25~30min.
[0013] In the preparation method as described above, the centrifugal treatment temperature is 0-4°C, the rotation speed is 4000-5000 rpm, and the time is 15-20 min.
[0014] In the preparation method as described above, the mass volume ratio of the FeCl3·6H2O to the extracellular polymer mixture is 0.1-0.5%.
[0015] The preparation method as described above, wherein the process of mixing the first product, sodium alginate, polyvinyl alcohol and water comprises the following steps:
[0016] Dissolving sodium alginate and polyvinyl alcohol in water respectively to form a sodium alginate solution and a polyvinyl alcohol solution; then mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution;
[0017] dispersing the first product in the mixed solution;
[0018] Wherein, the mass volume concentration of sodium alginate in the sodium alginate solution is 1-3%;
[0019] The mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1-3%;
[0020] The mass volume concentration of the first product in the mixed solution is 0.1-0.3%.
[0021] The preparation method as described above, wherein the mass volume concentration of calcium chloride in the calcium chloride solution is 1-5%.
[0022] The preparation method as described above, wherein the vacuum freeze drying is performed at a temperature of -30 to -40°C for 24 to 48 hours;
[0023] The particle size of the magnetite-loaded extracellular polymer hydrogel material is 3-5 mm.
[0024] The second aspect of the present invention provides an extracellular polymer material loaded with magnetite, which is prepared by the preparation method described in the first aspect.
[0025] The third aspect of the present invention provides an application method of an extracellular polymer material loaded with magnetite, wherein the extracellular polymer material loaded with magnetite is added to an aerobic granular sludge reactor;
[0026] The magnetite-loaded extracellular polymer material is prepared by the preparation method described in the first aspect or is the magnetite-loaded extracellular polymer material described in the second aspect.
[0027] In the application method as described above, the dosage of the extracellular polymer material loaded with magnetite is 0.5-2 g / L.
[0028] The implementation of the present invention has at least the following beneficial effects:
[0029] The preparation method of the extracellular polymer material loaded with magnetite provided by the present invention is to make the extracellular polymer in the residual sludge and FeCl3·6H2O into a hydrogel material. Through the synergistic effect of the two, on the one hand, it can act as a reinforcing agent to promote and accelerate the aggregation of particulate matter in the sludge to achieve sludge granulation, which helps to improve the system stability and pollution removal efficiency. On the other hand, it can effectively solve the problem of resource recovery of a large amount of residual sludge generated by sewage treatment plants and achieve sludge reduction. Secondly, the residual sludge, magnetite and other materials used in the present invention are non-toxic and harmless materials and will not cause secondary pollution. In addition, the above-mentioned preparation method is simple and easy to operate, which helps to reduce production costs.
[0030] The extracellular polymer material loaded with magnetite provided by the invention can effectively and stably promote the granulation of sludge.
[0031] The application method of the extracellular polymer material loaded with magnetite provided by the present invention is to apply the extracellular polymer material loaded with magnetite in an aerobic granular sludge reactor, which helps to promote the formation of aerobic granular sludge and improve the stability and pollution removal efficiency of the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a flow chart of a method for preparing an extracellular polymer material loaded with magnetite in one embodiment of the present invention;
[0033] Figure 21 is a structural diagram of an SBR reactor in one embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] like Figure 1 As shown, the first aspect of the present invention provides an extracellular polymer material loaded with magnetite, comprising the following steps: mixing excess sludge with a sodium chloride solution and performing a heating treatment to dissociate the extracellular polymer in the excess sludge to obtain a mixed solution; centrifuging the mixed solution and filtering the supernatant through a filter membrane to obtain an extracellular polymer mixed solution; adding FeCl3·6H2O to the extracellular polymer mixed solution, adjusting the pH to 7.5-8, stirring under ultrasonic action until the powder is completely dissolved, adjusting the pH to neutral, and performing vacuum freeze-drying to obtain a first product; mixing the first product, sodium alginate, polyvinyl alcohol and water, and then dropping a calcium chloride solution into the mixture for gelation to obtain hydrogel beads; and vacuum freeze-drying the hydrogel beads to obtain an extracellular polymer hydrogel material loaded with magnetite.
[0036] Residual sludge refers to solid waste discharged from a sedimentation tank (or sedimentation area), and the residual sludge contains a part of the microorganisms and metabolites in the activated sludge. Specifically, the residual sludge of the present invention can be obtained by discharging from the dewatering workshop, aerobic tank or secondary sedimentation tank of a sewage treatment plant. Sludge is divided into flocculent sludge or granular sludge. Flocculent sludge refers to tiny granular substances suspended in water, which are flocculent or colloidal in shape; granular sludge, also known as bottom mud, refers to granular sediment accumulated at the bottom of the water body or in a sedimentation tank.
[0037] Specifically, activated sludge refers to flocs containing various aerobic microbial groups that are propagated in aeration tanks. Since activated sludge contains a large number of microorganisms, in the secondary biochemical treatment of sewage, wastewater containing organic matter is brought into contact with activated sludge containing a large number of microorganisms through aeration, and the organic matter in the wastewater is decomposed and degraded during the growth and metabolism of the microorganisms. In this process, microorganisms continuously consume organic matter in the wastewater, and are also accompanied by the aging and death of microorganisms. When these dead microorganisms and other substances accumulate to a certain amount, they need to be removed by sedimentation or filtration to maintain the stable operation of the activated sludge system. The removed sludge is the residual activated sludge.
[0038] Residual sludge contains not only active microbial organisms, but also a large amount of organic matter in the form of extracellular polymers (EPS). EPS is a high molecular organic substance or polymer released by microorganisms under specific conditions, usually attached to the cell wall surface of bacteria, and its main components are protein (PN), polysaccharides (PS), DNA, humic acid and lipids.
[0039] In the present invention, before the excess sludge is mixed with the sodium chloride solution for heat treatment, the excess sludge is washed and centrifuged three times with the first sodium chloride solution to remove impurities on the surface of the excess sludge. The washed excess sludge is then dissolved in the second sodium chloride solution for heat treatment. During the heat treatment process, the extracellular polymers in the excess sludge are dissociated to obtain a mixed solution.
[0040] The mixed solution is centrifuged to remove impurities, and the supernatant is filtered through a filter membrane to obtain an extracellular polymer mixed solution. In other words, the extracellular polymer mixed solution contains a large amount of extracellular polymers.
[0041] Vacuum freeze drying is a method of freezing the above-mentioned mixed materials into solids, and using the sublimation properties of water under low temperature and low pressure conditions to dehydrate the materials at low temperature to achieve drying. Since vacuum freeze drying is carried out in a low temperature and low oxygen environment, most biological reactions are stagnant, and there is no liquid water in the treatment process. The water directly sublimates in a solid state, so that the original structure and shape of the material are protected to the greatest extent, and the first product is finally obtained, that is, extracellular polymers loaded with magnetite (Fe3O4@EPS).
[0042] The first product, sodium alginate, polyvinyl alcohol and water are mixed, and then calcium chloride solution is dropped into the mixture for gelation to obtain hydrogel beads; the hydrogel beads are vacuum freeze-dried to obtain an extracellular polymer hydrogel material loaded with magnetite. By introducing sodium alginate, polyvinyl alcohol and calcium chloride solution, the gel is promoted to wrap on the surface of Fe3O4@EPS, forming hydrogel particles of a certain size, which are convenient for being put into the aerobic granular sludge reactor and also convenient for collection for reuse.
[0043] According to the research of the present invention, the above-mentioned extracellular polymer material loaded with magnetite is applied to an aerobic granular sludge reactor, which can effectively and stably promote the granulation of sludge, improve the stability and pollution removal efficiency of the system, and help reduce production costs. This is because the extracellular polymer in the residual sludge is made into a hydrogel material with magnetite, and the extracellular polymer can be wrapped around the magnetite. At this time, under the joint action of the extracellular polymer and magnetite, it can be used as a matrix to maintain the structure of aerobic granular sludge and wrap the mixed microbial community to make it gather together. On the one hand, the viscous nature of the extracellular polymer is conducive to the mutual agglomeration of microorganisms; on the other hand, magnetite can neutralize the negative charge on the surface of the extracellular polymer, not only can the extracellular polymer be wrapped around the magnetite, but the polysaccharide contained in the extracellular polymer is hydrophilic, which can further increase the positive charge content, and can neutralize the negative charge on the surface of most cells to reduce the electrostatic repulsion between cells to achieve sludge granulation. Therefore, the present invention promotes sludge granulation through the synergistic effect of extracellular polymer and magnetite, which helps to improve system stability and pollution removal efficiency.
[0044] In addition, the present invention uses excess sludge as raw material, which can effectively solve the problem of resource recovery of a large amount of excess sludge generated by sewage treatment plants and achieve sludge reduction. Moreover, excess sludge, magnetite and other materials are non-toxic and harmless materials and will not cause secondary pollution.
[0045] In some embodiments, the mass volume concentration of the sodium chloride solution is 0.8-1%, for example 0.8%, 0.82%, 0.85%, 0.88%, 0.9%, 0.92%, 0.95%, 0.98%, 1% or a range consisting of any two thereof; the heating treatment temperature is 75-85°C, for example 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C or a range consisting of any two thereof; the time is 25-30 min, for example 25 min, 26 min, 27 min, 28 min, 29 min, 30 min or a range consisting of any two thereof.
[0046] In some embodiments, the temperature of the centrifugal treatment is 0-4°C, for example, 0°C, 1°C, 2°C, 3°C, 4°C or a range consisting of any two thereof; the rotation speed is 4000-5000rpm, for example, 4000rpm, 4100rpm, 4200rpm, 4300rpm, 4400rpm, 4500rpm, 4600rpm, 4700rpm, 4800rpm, 4900rpm, 5000rpm, or a range consisting of any two thereof; the time is 15-20min, for example, 15min, 16min, 17min, 18min, 19min, 20min or a range consisting of any two thereof.
[0047] In some embodiments, the mass volume ratio of the FeCl3·6H2O to the extracellular polymer mixture is 0.1-0.5%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two thereof.
[0048] In some embodiments, the process of mixing the first product, sodium alginate, polyvinyl alcohol and water comprises the following steps: dissolving sodium alginate and polyvinyl alcohol in water respectively to form a sodium alginate solution and a polyvinyl alcohol solution; then mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution; dispersing the first product in the mixed solution; wherein the mass volume concentration of sodium alginate in the sodium alginate solution is 1-3%, for example, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two thereof; the mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1-3%, for example, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two thereof; the mass volume concentration of the first product in the mixed solution is 0.1-0.3%, for example, 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or a range consisting of any two thereof.
[0049] In some embodiments, the mass volume concentration of calcium chloride in the calcium chloride solution is 1-5%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5% or a range consisting of any two thereof.
[0050] In some embodiments, the vacuum freeze-drying temperature is -30~-40°C, for example, -30°C, -32°C, -34°C, -36°C, -38°C, -40°C or a range consisting of any two thereof; the time is 24~48h, for example, 24h, 26h, 28h, 30h, 35h, 40h, 45h, 48h or a range consisting of any two thereof; the particle size of the extracellular polymer hydrogel material loaded with magnetite is 3~5mm, for example, 3mm, 3.2mm, 3.5mm, 3.8mm, 4mm, 4.2mm, 4.5mm, 4.8mm, 5mm or a range consisting of any two thereof.
[0051] The second aspect of the present invention provides an extracellular polymer material loaded with magnetite, which is prepared by the preparation method provided by the first aspect.
[0052] The third aspect of the present invention provides an application method of an extracellular polymer material loaded with magnetite, wherein the extracellular polymer material loaded with magnetite is added to an aerobic granular sludge reactor; the extracellular polymer material loaded with magnetite is prepared by the preparation method provided by the first aspect or the extracellular polymer material loaded with magnetite provided by the second aspect.
[0053] The present invention does not limit the specific type of the aerobic granular sludge reactor. For example, the aerobic granular sludge reactor may be a sequencing batch reactor (SBR reactor).
[0054] Specifically, the tank body of the aerobic granular sludge reactor is provided with a stirring unit and an aeration unit, an aeration pipe is provided at the bottom, and an inlet pipe and an outlet pipe are provided on the tank body of the aerobic granular sludge reactor. The outlet pipe can be arranged in the middle of the tank body, and an outlet valve is arranged on the outlet pipe, and an inlet valve is arranged on the inlet pipe. The stirring unit and the aeration unit are both provided with valves for controlling the switch.
[0055] The aerobic granular sludge reactor can be operated in anaerobic / aerobic / anoxic mode, where the anaerobic section only provides stirring, the stirring speed is 200~250 rpm, and the operation cycle is 4~6h. The volume of water discharged from the aerobic granular sludge reactor in each cycle accounts for 40-60% of the effective volume of the entire reactor.
[0056] The aerobic granular sludge reactor contains wastewater to be treated and inoculated sludge. The inoculated sludge can be selected from the activated sludge in the dewatering workshop, secondary sedimentation tank or aerobic tank of the sewage treatment plant. The activated sludge is flocculent sludge. After the inoculated sludge is retrieved, it is first air-dried for 1 day and then added to the aerobic granular sludge reactor. The initial concentration of the inoculated sludge is controlled at 5000~6000mg / L. The extracellular polymer material loaded with magnetite is added to the aerobic granular sludge reactor in a certain proportion, and the particle size, sedimentation performance and pollutant removal efficiency of the activated sludge are observed throughout the process, and the influence of the extracellular polymer material loaded with magnetite on the granulation process of aerobic sludge is monitored.
[0057] In some embodiments, the dosage of the extracellular polymer material loaded with magnetite is 0.5~2 g / L, for example, 0.5 g / L, 0.8 g / L, 1.0 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L, 1.8 g / L, 2 g / L or a range consisting of any two of them.
[0058] The present invention will be further described below by means of specific examples and comparative examples.
[0059] Example 1
[0060] 1. Preparation of extracellular polymeric materials loaded with magnetite
[0061] S1. Obtain the residual sludge from the sludge discharged from the dewatering workshop, aerobic tank or secondary sedimentation tank of the sewage treatment plant, wash and centrifuge the obtained residual sludge with 0.9% sodium chloride solution for 3 times to remove impurities on the surface of the residual sludge; dissolve the washed residual sludge in 0.9% sodium chloride solution, and heat it in a water bath at 80°C for 30 minutes; after the heating is completed, wait for the residual sludge mixed liquid to cool, centrifuge it at 4°C and 5000rpm for 20 minutes, take out the supernatant, and filter the supernatant through a 0.45μm filter membrane to obtain an extracellular polymer mixed liquid;
[0062] S2. Dissolve 2.5g FeCl3·6H2O in 500mL of extracellular polymer solution, and the mass volume ratio of FeCl3·6H2O to the extracellular polymer solution is 0.5%. Stir thoroughly under ultrasound until completely mixed, and adjust the pH to neutral. Then pour the resulting mixed solution into a stainless steel reaction vessel and incubate in a 200℃ high-pressure reactor for 24h. Then centrifuge the polymerized black solid-liquid mixture at 5000rpm for 5min, and centrifuge it alternately with deionized water and anhydrous ethanol for 3 times. The resulting solid sediment is dried in a vacuum drying oven at 80°C for 24 hours and passed through a 100-mesh sieve to obtain the first product of Fe3O4@EPS;
[0063] S3, dissolve sodium alginate (SA) and polyvinyl alcohol (PVA) in deionized water, respectively, and obtain sodium alginate solution and polyvinyl alcohol solution by magnetic stirring, wherein the mass volume concentration of sodium alginate in the sodium alginate solution is 2%, and the mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1%. The two solutions are mixed and stirred for 12 hours to obtain a mixed solution; a quantitative amount of Fe3O4@EPS first product is dispersed in the above mixed solution for 12 hours, and the mass volume concentration of Fe3O4@EPS first product in the mixed solution is 0.3%, and then dripped into CaCl2 solution for gelation treatment for 24 hours to obtain hydrogel beads, and the mass volume concentration of calcium chloride in the calcium chloride solution is 2%; repeatedly rinse the hydrogel beads, and dry them by freeze drying to obtain an extracellular polymer material loaded with magnetite (Fe3O4@EPS composite hydrogel material). The vacuum freeze drying temperature is -40℃, the time is 24 hours, and the particle size of the extracellular polymer hydrogel material loaded with magnetite is 4mm.
[0064] 2. Application of extracellular polymer materials loaded with magnetite
[0065] The columnar SBR reactor made of organic glass has an inner diameter of 10 cm, a height of 32 cm, an effective volume of 2.3 L, and a height-to-diameter ratio of 3. The SBR reactor is fed with water from the top, and an aeration head is installed at the bottom to connect the aeration pump for aeration. A water outlet valve is installed in the middle of the reactor. The reactor operates in anaerobic / aerobic / anoxic mode. The agitator is used to provide stirring during the static sedimentation and before the water is discharged. The stirring speed is about 250 rpm. The structural diagram of the SBR reactor is shown in the figure below. Figure 2 As shown;
[0066] The reactor operation cycle is 6 hours, including 2 minutes of water inlet, 120 minutes of anaerobic, 90 minutes of aerobic, 123-133 minutes of anoxic, 5-15 minutes of static sedimentation, and 10 minutes of water outlet. It runs 4 cycles per day. The reactor water inlet, stirring, aeration, water outlet and lighting are all connected to the microcomputer control switch to maintain the normal operation of the reactor. The volume exchange ratio of the reactor is 50%, and the hydraulic retention time is 12 hours.
[0067] Artificially simulate domestic sewage as the influent of the SBR reactor, and the influent COD, NH4 + -N and TP concentrations were controlled at 211±18.5, 22±1.2 and 3.21±0.17 mg / L. An appropriate amount of activated sludge was taken from the aerobic tank of the sewage treatment plant as inoculum sludge, and the inoculum sludge was placed in the reactor to make the initial sludge concentration MLSS 5500 mg / L and the inoculum sludge volume index 104.34 mg / L, and the static sedimentation time was gradually shortened to select granular sludge;
[0068] The Fe3O4@EPS composite hydrogel material was added to the influent at a dosage of 1 g / L, and the particle size of the granular sludge and the removal rate of carbon, nitrogen and phosphorus in the reactor were measured regularly;
[0069] The results showed that at 30 days, the average particle size of the sludge reached 570 μm, the chemical oxygen demand (COD) removal rate was above 90%, the average total nitrogen (TIN) removal rate was 83.8%, and the total phosphorus (TP) removal rate was 85.1%.
[0070] Example 2
[0071] The preparation process is basically the same as that in Example 1, except that Fe3O4@EPS composite hydrogel material is added to the influent water at a dosage of 2 g / L, and other conditions remain unchanged.
[0072] The results showed that at 30 days, the average sludge particle size reached 620 μm, the COD removal rate was above 90%, the average TIN removal rate was 85.4%, and the TP removal rate was 86.8%.
[0073] Example 3
[0074] The preparation process is basically the same as that of Example 2, except that 0.5 g of FeCl3·6H2O is dissolved in 500 mL of extracellular polymer solution, and the mass volume ratio of FeCl3·6H2O to the extracellular polymer solution is 0.1%. Other conditions remain unchanged.
[0075] The results showed that at 30 days, the average sludge particle size reached 555 μm, the COD removal rate was above 90%, the average TIN removal rate was 82.7%, and the TP removal rate was 83.1%.
[0076] Example 4
[0077] The preparation process is basically the same as that of Example 2, except that 1.5 g of FeCl3·6H2O is dissolved in 500 mL of extracellular polymer solution, and the mass volume ratio of FeCl3·6H2O to the extracellular polymer solution is 0.3%. Other conditions remain unchanged.
[0078] The results showed that at 30 days, the average sludge particle size reached 595 μm, the COD removal rate was above 90%, the average TIN removal rate was 83.5%, and the TP removal rate was 84.9%.
[0079] Comparative Example 1
[0080] 1. The preparation process of the hydrogel material is as follows: sodium alginate (SA) and polyvinyl alcohol (PVA) are dissolved in deionized water respectively, and a sodium alginate solution and a polyvinyl alcohol solution are obtained by magnetic stirring, wherein the mass volume concentration of sodium alginate in the sodium alginate solution is 2%, and the mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1%. The two solutions are mixed and stirred for 12 hours to obtain a mixed solution; then a CaCl2 solution is dropped into the mixed solution for gelation treatment for 24 hours to obtain hydrogel beads; the hydrogel beads are repeatedly rinsed and dried by freeze drying to obtain a hydrogel material, and the mass volume concentration of calcium chloride in the calcium chloride solution is 2%.
[0081] 2. The application process is basically the same as that in Example 1, except that the Fe3O4@EPS composite hydrogel material in Example 1 is replaced by the hydrogel material of this comparative example. Specifically, the hydrogel material is added to the influent in this comparative example at a dosage of 2 g / L, and the particle size of the granular sludge in the reactor and the carbon, nitrogen and phosphorus removal rate are regularly measured.
[0082] The results showed that at 30 days, the average sludge particle size was 390 μm, the COD removal rate was above 90%, the average TIN removal rate was 79.4%, and the TP removal rate was 80.3%.
[0083] Comparative Example 2
[0084] Sodium alginate (SA) and polyvinyl alcohol (PVA) were dissolved in deionized water, respectively, and magnetic stirring was used to obtain sodium alginate solution and polyvinyl alcohol solution, respectively, wherein the mass volume concentration of sodium alginate in the sodium alginate solution was 2%, and the mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution was 1%. The two solutions were mixed and stirred for 12 hours to obtain a mixed solution; a quantitative FeCl3·6H2O sample was dispersed in the above mixed solution for 12 hours, and the mass volume concentration of FeCl3·6H2O in the mixed solution was 0.3%, and then it was dropped into CaCl2 solution for gelation treatment for 24 hours to obtain hydrogel beads, and the mass volume concentration of calcium chloride in the calcium chloride solution was 2%; the hydrogel beads were repeatedly rinsed and dried by freeze-drying to obtain Fe3O4 composite hydrogel material. The application process is basically the same as that in Example 1, except that the Fe3O4@EPS composite hydrogel material in Example 1 is replaced by the Fe3O4 composite hydrogel material in this comparative example. Specifically, in this comparative example, Fe3O4 composite hydrogel material is added to the influent water at a dosage of 2 g / L, and the particle size of the granular sludge in the reactor and the carbon, nitrogen and phosphorus removal rate are regularly measured.
[0085] The results showed that at 30 days, the average sludge particle size was 540 μm, the COD removal rate was above 90%, the average TIN removal rate was 82.2%, and the TP removal rate was 82.7%.
[0086] Comparative Example 3
[0087] 500 mL of the extracellular polymer solution was incubated in a high-pressure reactor at 200 ° C for 24 h. The solid-liquid mixture was then centrifuged at 5000 rpm for 5 min and centrifuged alternately with deionized water and anhydrous ethanol for 3 times. The resulting solid sediment was dried in a vacuum drying oven at 80 ° C for 24 hours and passed through a 100 mesh sieve to obtain EPS solid product.
[0088] Sodium alginate (SA) and polyvinyl alcohol (PVA) were dissolved in deionized water, respectively, and magnetic stirring was used to obtain sodium alginate solution and polyvinyl alcohol solution, respectively, wherein the mass volume concentration of sodium alginate in the sodium alginate solution was 2%, and the mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution was 1%. The two solutions were mixed and stirred for 12 hours to obtain a mixed solution; a quantitative EPS solid product was dispersed in the above mixed solution for 12 hours, and the mass volume concentration of EPS in the mixed solution was 0.3%, and then it was dropped into a CaCl2 solution for gelation treatment for 24 hours to obtain hydrogel beads, and the mass volume concentration of calcium chloride in the calcium chloride solution was 2%; the hydrogel beads were repeatedly rinsed and dried by freeze-drying to obtain an extracellular polymer composite hydrogel material. The application process is basically the same as that in Example 1, except that the Fe3O4@EPS composite hydrogel material in Example 1 is replaced by the extracellular polymer composite hydrogel material of this comparative example. Specifically, the extracellular polymer composite hydrogel material is added to the influent in this comparative example at a dosage of 2 g / L, and the particle size of the granular sludge in the reactor and the carbon, nitrogen and phosphorus removal rate are regularly measured.
[0089] The results showed that at 30 days, the average sludge particle size was 490 μm, the COD removal rate was above 90%, the average TIN removal rate was 81.5%, and the TP removal rate was 81.9%.
[0090] It can be seen that the Fe3O4@EPS composite hydrogel material of Examples 1-4 has a promoting effect on the enhanced aerobic granular sludge. After adding this material, the particle size of the aerobic granular sludge system is significantly increased and the pollutant removal rate is also improved.
[0091] The preferred specific embodiments and experimental verification of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the protection scope of the present invention.
Claims
1. A method for preparing an extracellular polymer material loaded with Fe3O4, characterized in that: The following steps are involved: The excess sludge is mixed with a sodium chloride solution and subjected to a heating treatment to dissociate the extracellular polymers in the excess sludge to obtain a mixed solution; the mixed solution is centrifuged and the supernatant is filtered through a filter membrane to obtain an extracellular polymer mixed solution; Add FeCl3·6H2O to the extracellular polymer mixture, stir under ultrasound until the powder is completely dissolved, adjust the pH to neutral, incubate at high temperature and high pressure, centrifuge and freeze-dry in vacuum to obtain the first product; The first product, sodium alginate, polyvinyl alcohol and water are mixed, and then a calcium chloride solution is dropped into the mixture for gelation to obtain hydrogel beads; the hydrogel beads are vacuum freeze-dried to obtain an extracellular polymer hydrogel material loaded with magnetite.
2. The preparation method according to claim 1, characterized in that: The mass volume concentration of sodium chloride solution is 0.8~1%; The heating treatment temperature is 75~85℃ and the time is 25~30min.
3. The preparation method according to claim 1, characterized in that: The temperature of the centrifugal treatment is 0~4°C, the speed is 4000~5000rpm, and the time is 15~20min.
4. The preparation method according to claim 1, characterized in that: The mass volume ratio of the FeCl3·6H2O and the extracellular polymer mixed solution is 0.1-0.5%.
5. The preparation method according to claim 1, characterized in that: The process of mixing the first product, sodium alginate, polyvinyl alcohol and water comprises the following steps: Dissolving sodium alginate and polyvinyl alcohol in water respectively to form a sodium alginate solution and a polyvinyl alcohol solution; then mixing the sodium alginate solution and the polyvinyl alcohol solution to obtain a mixed solution; dispersing the first product in the mixed solution; Wherein, the mass volume concentration of sodium alginate in the sodium alginate solution is 1-3%; The mass volume concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1-3%; The mass volume concentration of the first product in the mixed solution is 0.1-0.3%.
6. The preparation method according to claim 1, characterized in that: The mass volume concentration of calcium chloride in the calcium chloride solution is 1-5%.
7. The preparation method according to claim 1, characterized in that: The vacuum freeze drying temperature is -30 to -40°C and the time is 24 to 48 hours; The particle size of the magnetite-loaded extracellular polymer hydrogel material is 3-5 mm.
8. An extracellular polymer material loaded with magnetite, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.
9. A method for applying an extracellular polymer material loaded with magnetite, characterized in that: adding the extracellular polymer material loaded with magnetite into an aerobic granular sludge reactor; The magnetite-loaded extracellular polymer material is prepared by the preparation method described in any one of claims 1 to 7 or the magnetite-loaded extracellular polymer material described in claim 8.
10. The application method according to claim 9, characterized in that: The dosage of the extracellular polymer material loaded with magnetite is 0.5-2 g / L.
Citation Information
Patent Citations
Method for quickly starting anaerobic ammonia oxidation reactor through immobilization of anaerobic ammonia oxidation microorganisms
CN113800651A
Preparation method of sludge extracellular polymeric substance composite nano zero-valent iron
CN113929195A
Preparation method and application of composite core for culturing anaerobic granular sludge
CN114230018A
Preparation method of sludge-based biochar loaded nano-iron based on extracellular polymeric substance regulation
CN114797777A
Hybrid hydrogel carrier for high-salinity wastewater treatment and preparation method thereof
US20220119599A1
Cited By
Method for synchronously promoting formation of aerobic granular sludge and relieving membrane pollution
CN121158955A
Hydrogel precursor-based aerobic granular sludge as well as preparation method and application thereof
CN121948687A
An aerobic granular sludge based on a hydrogel precursor, its preparation method and application
CN121948687B